2007
DOI: 10.1159/000106763
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal <i>Clostridium perfringens</i> Sepsis in a Patient with Granulocytopenia

Abstract: We present a lethal case of fulminant puerperal sepsis with massive hemolysis after cesarean section in a patient with intermittent granulocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…A search was conducted using PubMed for all published cases of C perfringens septicemia resulting in massive hemolysis, using the medical subject heading terms “clostridia,” “clostridial sepsis,” and “hemolysis.” All case reports, series, and reviews were selected, including the 2 most comprehensive literature reviews published to date, by van Bunderen et al 5 This brought the total number of published cases to 50. 8 58 There were no exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…A search was conducted using PubMed for all published cases of C perfringens septicemia resulting in massive hemolysis, using the medical subject heading terms “clostridia,” “clostridial sepsis,” and “hemolysis.” All case reports, series, and reviews were selected, including the 2 most comprehensive literature reviews published to date, by van Bunderen et al 5 This brought the total number of published cases to 50. 8 58 There were no exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…32 MIH has classically been reported in cases of post-abortion and postpartum infections, and gas gangrene. 22,23,31,33,34 Improvement in medical care has decreased the incidence of these entities. 22,34,35 However, new and more aggressive treatment of patients with malignant diseases has increased the occurrence of serious infections, including clostridial sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,31,33,34 Improvement in medical care has decreased the incidence of these entities. 22,34,35 However, new and more aggressive treatment of patients with malignant diseases has increased the occurrence of serious infections, including clostridial sepsis. 22,36 Currently, MIH develops in patients with diabetes mellitus, immunodeficiency, and malignant neoplasms, especially those with colon cancers and hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…2 Clostridial sepsis has been infrequently reported to occur after invasive procedures that involve the gastrointestinal or hepatobiliary tracts, and after gynecological procedures or insertion of central lines. [13][14][15] The reported patient was elderly but did not have a history of recent gastrointestinal, gynecological or hepatobiliary surgery, liver failure or an immunocompromised state. The mastectomy had been performed some years previously, and there was no evidence of recurrence or of metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found the mean age of patients who contracted C. perfringens sepsis was 71 years 2 . Clostridial sepsis has been infrequently reported to occur after invasive procedures that involve the gastrointestinal or hepatobiliary tracts, and after gynecological procedures or insertion of central lines 13–15 . The reported patient was elderly but did not have a history of recent gastrointestinal, gynecological or hepatobiliary surgery, liver failure or an immunocompromised state.…”
Section: Discussionmentioning
confidence: 99%